2017
DOI: 10.1007/s40261-017-0591-3
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Use and Cost of Biological Drugs for Cancer Treatment: A 5-Year Picture from Southern Italy

Abstract: Background and ObjectivesConsidering the clinical and economic burden of biological and non-biological targeted therapies in cancer treatment, it is necessary to explore how these drugs are used in routine care in Italy and how they affect the sustainability of the National Health Services. This study aimed to investigate the prevalence of use and costs of biological and non-biological targeted therapies for cancer treatment in a general population of Southern Italy in the years 2010–2014.MethodsThis was a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As reported by other studies, 34,35 the costs of cancer care have risen dramatically in the past decade. Specifically, the prevalence of patients undergoing new oncological therapies and associated spending have more than doubled.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As reported by other studies, 34,35 the costs of cancer care have risen dramatically in the past decade. Specifically, the prevalence of patients undergoing new oncological therapies and associated spending have more than doubled.…”
Section: Discussionmentioning
confidence: 62%
“…15 Finally, a recent study by Giuliani et al demonstrated that durvalumab could be considered cost-effective, with an ICER of €3717 per month of PFS gained. 16,33 As reported by other studies, 34,35 the costs of cancer care have risen dramatically in the past decade. Specifically, the prevalence of patients undergoing new oncological therapies and associated spending have more than doubled.…”
Section: Discussionmentioning
confidence: 71%